Chromosomal study of Khawia abbottinae (Cestoda: Caryophyllidea): karyotype and localization of telomeric and ribosomal sequences after fluorescence in situ hybridization (FISH) - Orosová, Martina; Provazníková, Irena; Xi, Bing Wen; Oros, Mikuláš (Parasitology research, 2019)
An original cytogenetic study combining classical karyotype analysis and modern fluorescence in situ hybridization using telomeric (TTAGGG)n and ribosomal sequences (18S rDNA) was performed in Khawia abbottinae (Cestoda, Caryophyllidea), a parasite of Chinese false gudgeon (Abbottina rivularis) from China. Analyses based on conventional Giemsa staining, DAPI, YOYO-1 dye, and silver (Ag) staining were also carried out. The karyotype is composed of eight pairs of metacentric and telocentric chromosomes (2n = 16, n=5m + 3t). Constitutive heterochromatin was mainly positioned at pericentromeric regions, and telomeric sequences (TTAGGG)n were restricted to the end of all chromosomes. In mitotic preparations stained with Giemsa, both homologues of chromosome pair 4 showed a distinct secondary constriction. FISH with rDNA probe confirmed that this secondary constriction contains a nucleolar organizer region (NOR). The process of spermatocyte meiosis and the dynamics of nucleolus degradation in dividing cell were scrutinized. The present study and its results enhance the limited knowledge on basic karyotype characteristics and 18S rDNA clusters location in caryophyllidean tapeworms.
Keywords: Animals; Ribosomes; ribozomální DNA; DNA, Ribosomal; Helminth Proteins; Cestoda; karyotypizace; China; Karyotyping; telomery; Cyprinidae; Telomere; heterochromatin; Heterochromatin; karyotyp; DNA, Helminth; Chromosomes; DNA helmintů; Karyotype; Čína; ribozomy; hybridizace in situ fluorescenční; proteiny červů; zvířata; In Situ Hybridization, Fluorescence; chromozomy